A COMPARISON ON STUDENTS’ PERFORMANCE IN MATHEMATICS SUBJECT USING FUZZY LOGIC THEORY - Suriana Lasaraiya; Mohd Azrul Abd Rajak; Che Haziqah Che Hussin; Nurliyana Juhan, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The education system in Malaysia employs classical method in evaluation students’ progress performances during their foundation level. The result was obtained by adding all the assessments scored and was graded based on grade A, A-, B+, B, …, and F. Somehow, non-classical methods may be applied such as fuzzy logic, where it can be applied to many forms of decision making. This paper proposed evaluation on students’ performances by using fuzzy logic approach. The assessment score obtained based on their assignment, midterm examination and final term examination of 26 Agriscience students, in Preparatory Centre for Science and Technology (PPST), University Malaysia Sabah, UMS was carried out with fuzzy logic. Their results are calculated based on classical method and fuzzy logic approach, which is then compared and analysed. The comparison shows variation between classical and fuzzy logic approach in terms of their overall results.